Implementasi Data Mining Dengan Algoritma Nearest Neighbor Untuk Penentuan Kelayakan Area Pemasaran Baru Produk Baygon Pada PT. SRB Cabang Kabanjahe - Wanda Kurnia (JURIKOM (Jurnal Riset Komputer), 2019)
Marketing Area is a region or environment that serves as a place of an enterprise activity to control the flow of goods and services to consumers with appropriate planning by creating and exchanging products with equivalent value. Data Mining is a process that employs one or more computer learning techniques to analyze or extract knowledge (Knoweldge) automatically. Nearest Neighbor is an approach to finding cases by calculating the proximity between a new case and an old case that is based on matching the weight of a number of features.